The Transformation of the Kafālah and Ḥawālah Contracts into the Muʻāwaḍah Contract Maṣlaḥah Perspective: An Analytical Study of DSN-MUI Fatwa - Aziem, Abdul; Arif Khan, M. Dawud; Hidayat, Hidayat (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research is motivated by the paradigm shift of kafālah and ḥawālah contracts within the Islamic finance industry in Indonesia. While classical jurisprudence categorizes these contracts as non-profit tabarruʻ (social) contracts, the fatwas issued by the National Sharia Council of the Indonesian Ulama Council (DSN-MUI) have transformed them into muʻāwaḍah (commercial) contracts through the implementation of ujrah (fees). This study aims to analyze the form of this contract transformation, examine the ijtihad methods and approaches employed by DSN-MUI, and explore the substance of maṣlaḥah (public interest) that validates this shift, particularly in supporting the halal economy and tourism ecosystem. The research employs a qualitative method with a library research design, utilizing content and conceptual analysis approaches on relevant fatwas. The results indicate that: (1) The transformation of kafālah and ḥawālah contracts in DSN-MUI fatwas substantively shifts them into ijārah (lease of services) or wakālah bi al-ujrah contracts, which is valid based on the principle of legal substantiality. (2) DSN-MUI utilizes the intiqā’ī (selective) ijtihad method combined with manhajī approaches, specifically at-taysīr al-manhajī (methodological facilitation) and iʻādah an-naẓar (re-evaluation) of classical legal causes (ʻillat). (3) The substance of maṣlaḥah in this transformation is manifested in mutual interest (sustainability of financial institutions), product flexibility (such as support for smart tourism), and the effectiveness of legal certainty within Indonesia's positive law.